1986
DOI: 10.1016/0198-8859(86)90047-9
|View full text |Cite
|
Sign up to set email alerts
|

Functional characterization of infiltrating T lymphocytes in human hepatic allografts

Abstract: We have employed recently developed techniques in T-cell culturing to study the nature and function of infiltrating hepatic allograft T cells. Using the rationale that intragraft T cells are activated during cell mediated damage to the allograft, we were able to show that these cells would propagate and remain functionally active in the presence of the T-cell growth factor, IL-2. In several instances, phenotypic analysis of cells grown in this manner was very similar to that found within the graft. Both prolif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2003
2003

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Functional a~alysis of.graftinfiltrating lymphocytes cultured from lIver sp.ecIm~ns during a rejection reaction have confirmed prolIferative and cytotoxic activity directed at these antigens (18).…”
Section: Pathologic Comparison Of Native Hepatectomies With Pbc and Fmentioning
confidence: 89%
“…Functional a~alysis of.graftinfiltrating lymphocytes cultured from lIver sp.ecIm~ns during a rejection reaction have confirmed prolIferative and cytotoxic activity directed at these antigens (18).…”
Section: Pathologic Comparison Of Native Hepatectomies With Pbc and Fmentioning
confidence: 89%
“…Alloreactive lymphocyte cultures were also propagated from human heart and liver core biopsies in the presence of IL-2 as previously reported (2,3]. Secondary proliferation of alloreaccive cells was assessed in a 3-day primed lymphocyte test (PLT), whereby 10 4 responder cells were incubated with 10 1 irradiated (2000 R) stimulator cells [12].…”
Section: Primed Lympho'y1e Test Testing Of Alloreacjive T Cel/s Allomentioning
confidence: 99%
“…T cells from transplanted tissues have demonstrated the presence of donorspecific lymphocytes in transplanted organs at various stages of rejection [1][2][3]. Donor-specific T cells have also been grown from transplant biopsies without any evidence of an ongoing or pending rejection episode as diagnosed clinically or histologically [4}.…”
mentioning
confidence: 99%
“…1,3 In liver transplantation, studies about the impact of HLA antigens have given contradictory results. 1,[4][5][6] However, there is evidence that HLA antigens are involved in cellular immune responses, 7,8 and that a high HLA class I expression, as well as specific HLA class II alleles, such as DQB1*0302, may be related to liver graft tolerance and rejection. 9,10 In regard to HLA-matching, previous studies reported that a total class I mismatch in combination with partial or complete class II match has lead to vanishing bile duct syndrome.…”
mentioning
confidence: 99%